Para além da acusatoriedade: passado e presente da investigação criminal no Brasil - Corrêa, Thiago Pinheiro (2019)
The Brazilian Criminal Justice System is often classified as “adversarial” instead as “inquisitorial”, dichotomy that has been used by the Supreme Court itself in a great number of cases. Nonetheless, there is little consensus about how police, prosecutors and courts interact one with another in the midst of this “adversarial” system and, specially, during criminal investigation. This work argues that the dichotomy “adversarial x inquisitorial” is not sufficient, as a theoretical tool, to explain the dynamic structure of the Brazilian Criminal Justice System. It stresses the relevance of the historical perspective of Brazilian criminal investigation and points out how the Brazilian Criminal Justice was reformed during the nineteenth century, time when relationship between “police and courts” was already discussed in Congress. It stresses the impact of the Brazilian Constitution of 1988 on criminal investigation and in the activities of police, prosecutors and courts.